An algebra problem by Sal Gard

Algebra Level 4

If the largest real root of x 6 4 x 4 2 x 3 + 4 x 2 + 4 x + 1 = 0 x^6-4x^4-2x^3+4x^2+4x+1=0 can be expressed as a + b c \dfrac{\sqrt a+b}{c} , with a a square-free and b b and c c are relatively prime, find ( a b c ) 2 + 1 {(abc)}^2+1


The answer is 101.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

James Wilson
Nov 15, 2017

Here was the method I used. Use synthetic division with -1 twice to get x 4 2 x 3 x 2 + 2 x + 1 = 0 x^4-2x^3-x^2+2x+1=0 . Then divide by x 2 x^2 , and regroup the terms to get ( x 2 2 + 1 x 2 ) + ( 2 x + 2 x ) + 1 = 0 ( x 1 x ) 2 2 ( x 1 x ) + 1 = 0 ( x 1 x 1 ) 2 = 0 x 2 x 1 = 0 (x^2-2+\frac{1}{x^2})+(-2x+\frac{2}{x})+1=0\Rightarrow (x-\frac{1}{x})^2-2(x-\frac{1}{x})+1=0\Rightarrow (x-\frac{1}{x}-1)^2=0 \Rightarrow x^2-x-1=0 . The larger root of this equation is 5 + 1 2 \frac{\sqrt{5}+1}{2} .

Sal Gard
Jun 17, 2016

Notice this should be the square of a function in order to be solved by immediate means. This will be proved later. By the rational root theorem, we can see 1 -1 is a root. Now consider a number such that x 2 x = 1 x^2-x=1 . By manipulation, we can see the roots of this and -1 would be added to a cubic that would be the square root. This can be done x 2 ( x 2 ) x 2 ( x ) = x 2 , x 2 ( x + 1 ) x ( x + 1 ) = x 2 , x 3 x = x + 1 x^2(x^2)-x^2(x)=x^2, x^2(x+1)-x(x+1)=x^2, x^3-x=x+1 or x 3 2 x 1 = 0 x^3-2x-1=0 . If we square this, we get the desired expression. Now we see of the roots of x 2 x = 1 x^2-x=1 , the golden ratio ( ( s q r t 5 (sqrt 5 +1)/2) is the largest. So the answer is 101 101 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...